Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria

Differential accumulation of vimentin fragments in preeclamptic placenta - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Cytoskeleton, 2017)
Preeclampsia is a pregnancy complication that is the result of abnormal placentation because of inadequate trophoblast invasion into spiral arteries that prevent normal blood flow to the placenta. We report the alteration in vimentin protein proteolysis in placenta of normotensive and preeclamptic women, which is known to have a role in many physiological functions other than its major function in the structural integrity of the cell. Placental proteome from normotensive (n=25) and preeclamptic pregnancies (n=25) showed eight differentially accumulated protein spots of vimentin (proteolytic fragments) by two-dimensional electrophoresis. Immunoblots of normotensive and preeclamptic placenta revealed a difference in proteolytic processing of vimentin. In particular, lower molecular weight vimentin fragments of 32 and 20 kDa were 3.3 and 2.6-fold (p<0.0001) higher, respectively, in preeclampsia compared with normotensive placenta.